How have retrovirus pseudotypes contributed to our understanding of viral entry? - Tarr, Alexander W.; King, Barnabas (Future Medicine, 2017)
Study of virus entry into host cells is important for understanding viral tropism and pathogenesis. Studying the entry of in vitro cultured viruses is not always practicable. Study of highly pathogenic viruses, viruses that do not grow in culture, and viruses that rapidly change phenotype in vitro can all benefit from alternative models of entry. Retrovirus particles can be engineered to display the envelope proteins of heterologous enveloped viruses. This approach, broadly termed ‘pseudotyping’, is an important technique for interrogating virus entry. In this perspective we consider how retrovirus pseudotypes have addressed these challenges and improved our understanding of the entry pathways of diverse virus species, including Ebolavirus, human immunodeficiency virus and hepatitis C virus.